UTILIZATION OF BIOFLOCS FROM NURSERY FOR FRESHWATER PRAWN (Macrobrachium rosenbergii) LARVAE REARING - Asep Sopian; Ikhsan Khasani; Fajar A (Widyariset, 2013)
The Bioflocs technology development in the aquaculture industry is very prospective due to many inheren benefits, especially for water quality control and nutrition substitution. This study aims to determine the effect of media bioflocs nursery for freshwater prawn (Macrobrachium rosenbergii) larvae rearing. The experiment design with completely randomized design was used in the study with 3 treatments and 6 replications. The treatment used were: A. without bioflocs addition (control), B. the addition of 5 ml bioflocs, and C. the addition of 10 ml bioflocs. The 1st day old larvae was used in the study and reared on a 60 l conical fiberglass at 50 ind/l of density. The main parameters were larvae development or larval stage index (LSI) and survival rate (SR). Based on the result of statistical analysis showed that the addition of bioflocs affected survival rate significantly (p<0.05) and the best survival values generated by the addition biofloc treatment as much as 5 ml.